Pré-tratamentos e digestão anaeróbia da palha de cana-de-açúcar - Rossi, Eduardo de (2015)
Considering the growing demand for fuels, particularly liquids, and the possibility of producing renewable fuels using materials previously discarded or underutilized, there is need to develop processes to the use of a material usually discarded and wide availability, especially in Brazil, its straw the sugarcane, which has already ban burning in some Brazilian states, and this maximizes its importance, given the need for allocation. Therefore, this work studied the modification chemical degradation generated by two forms of pre-treatment of straw sugarcane, using citric acid in an autoclave, and urea solution with sodium hydroxide at low temperature. The efficiency of modification of each treatment was followed by Fourier transform infrared spectroscopy and in the UV-visible region. The results showed that there are significant changes in the material studied, with degradation of lignin and hemicellulose and cellulose exposure to hydrolysis later. Spectroscopic techniques were effective in monitoring the changes caused by treatments. Already in the second stage, we attempted to biologically digest this material comparing fresh straw, straw pretreated with acid Citric, pretreated straw with urea and NaOH, and straw with both pre-treatments. Straw is delimited amounts of 0; 2.5; 5; 7.5 to 10% w / w. In all reactors was used 20% v / v inoculum. The inoculum consisted of 30% w / w poultry-to-bed and 70% of ARS. The experiment was conducted with greenhouses kept in mesophilic condition. It can be identified that to apply the pre-treatments proposed in the straw cane sugar, has a significant gain in production biogás.gSVR-1, and the proportions order to produce more biogas indicated when apply pre-treatments are 5 and 7.5% of straw in ARS. While the best results from digestion of straw cane sugar were obtained by pre-treating with acid Citric.